Walking pace and its association with osteoporosis and pathological fractures: insights from UK biobank - Hu, Qin; Liu, Haoran; Du, Yuchen; Duan, Runchen; Li, Linpeng; Yang, Daishui; Ouyang, Zhengxiao (Frontiers in Endocrinology, 2025)
BackgroundsOsteoporosis is a prevalent bone disease. Previous research has indicated that various forms of exercise have different protective effects on bone health, yet there are limited studies on the impact of walking pace on bone mineral density (BMD) and skeletal health. This study aims to investigate the correlation between usual walking pace and osteoporosis, including related fractures, while considering potential interactions with genetic vulnerability.MethodsSurvey responses from 348,334 participants in the UK Biobank were analyzed, obtaining information on usual walking pace, BMD, osteoporosis incidence, and genetic vulnerability. Multiple linear regression, Cox proportional hazards regression models, and stratified analysis methods were employed. A weighted genetic risk score for osteoporosis was calculated.ResultsCross-sectional analysis revealed a notable upward trend in BMD and a downward trend in the risk of osteoporosis and fractures from slow to brisk walking pace (P <0.001). Slow walking was associated with the highest risk of osteoporosis [hazard ratio (HR) 2.18, 95% confidence interval (CI) 2.03 - 2.34] and fractures (HR 2.25, 95% CI 1.79 - 2.81). Prospective analysis showed that brisk walking was significantly linked to reduced incident osteoporosis (HR 0.85, 95% CI 0.79 - 0.91) and fractures (HR 0.75, 95% CI 0.63 - 0.89) after excluding baseline cases.ConclusionsThe findings provide evidence that walking pace is closely related to the prevalence of osteoporosis and fracture incidence. Therefore, integrating walking into national physical activity initiatives and encouraging individuals to increase their walking pace could serve as an effective preventive measure against osteoporosis.